Bcl-2 expression and clinico-pathological correlations in invasive ductal carcinoma of the breast - Al-Joudi, Fawwaz S.,; Iskandar, Zulkarnain A., (Penerbit UKM, 2010)
Bcl-2 is an anti-apoptotic protein belonging to a family of proteins that act as regulators of apoptosis in mammalian cells. Bcl-2 expression has previously been reported in normal breast ductal cells and its involvement in the hormonal regulation of hyperplasia and involution was further suggested, and it was thought to be expressed through hormonedependent pathways. Bcl-2 is a cytoplasmic oncoprotein which is highly expressed in human solid tumours. In breast cancer cells, however, Bcl-2 expression is down regulated, the exact mechanism and the effects of which are not clearly defined, as bcl-2 expression appears to be inversely correlated with the presence of p53 mutations. This work aimed at investigating the expression of bcl-2 in invasive ductal carcinoma of the breast utilizing an immunohistochemistry assay as well as studying the clinical correlations of bcl-2. Bcl-2 was detected in 43.7% of 382 invasive ductal carcinoma study cases. Its expression correlated positively, with lower age of patients, higher histological grades, large tumour sizes, estrogen receptor positivity and progesterone receptor negativity. However, the statistical correlations were weak. With the data obtained, it was found that the expression of bcl-2 correlated with unfavourable prognoses. Furthermore, bcl-2 detection alone may not be very helpful in consolidating a clinical diagnosis.